Deficiency of CD147 Attenuated Non-alcoholic Steatohepatitis Progression in an NLRP3-Dependent Manner - Zhang, Tian; Li, Hao; Wang, Ke; Xu, Bing; Chen, Zhi-Nan; Bian, Huijie (Frontiers in Cell and Developmental Biology, 2020)
CD147 is a transmembrane glycoprotein belonging to the immunoglobulin superfamily. CD147 overexpression has been reported to facilitate the development of hepatocellular carcinoma (HCC) and influence immunologic disorders. Although increased expression of CD147 was reported in nonalcoholic steatohepatitis (NASH), functions of CD147 in NASH have not been evaluated. Firstly, we confirmed that CD147 expression was increased in the liver tissues from MCD diet-induced NASH model mice and NASH patients. Mice with hepatocyte-specific CD147 deletion exhibited attenuated NASH phenotypes, including reduced steatosis, liver injury, hepatocyte apoptosis and inflammatory cytokines IL-1β/IL-18 secretion. Along with MCD diet, NLRP3 expression was increased gradually, in accordance with CD147 expression. Furthermore, CD147 deletion inhibited the NF-κB/NLRP3 signaling pathway in both MCD diet-induced mice and primary hepatocytes. Finally, CypA inhibitor TMN355 attenuated liver steatosis and injury and inhibited NF-κB/NLRP3 signaling pathway. Therefore, our results suggest that CD147 played a vital role in NASH pathogenesis by regulating the inflammatory response, and CypA/CD147 could be attractive therapeutic targets for NASH treatment.